Benefits of 8-week fitness programs on health and fitness parameters (Beneficios de los programas de fitness de ocho semanas en parámetros de salud y fitness) - Campos, Francisco; González-Víllora, Sixto; González Gómez, David; Martins, Fernando Manuel Lourenço (Retos, 2019)
Abstract: considering health and fitness enhancements as the main reasons for engaging in physical activity, the growing number of sport participants in health or fitness centers, as well as the trends in fitness in 2018, the aim of this work is to analyze the benefits of five different fitness programs: G1) diet and no-exercise; G2) diet and weight training (WT); G3) diet and high intensity power training (HIPT); G4) diet and indoor cycling; G5) diet and boxing; on health and fitness parameters. Five groups were created and participants were evenly and randomly distributed (G1 to G5: n = 50; 25 f, 33.96 ± 3.42 years). In the first analysis, paired samples t test was used to compare the dependent variables within each group separately, from pre-to post-test. In the second analysis, one-way ANOVA was used to compare the selected variables between the different groups, at pre-and post-test; following, post-hoc continuation test was performed where the ANOVA detected significant differences. When the main reason for practice was loss of weight and fat mass, HIPT and boxing produced better results than the other programs. For the increase of fat-free mass, WT presented the best results. Regarding fitness parameters, WT was the activity that presented higher results in the increase of lower explosive strength and upper maximum strength, with significant statistical differences between pre- and post-test. Fitness instructors can use this information to adapt, choose and prescribe adequate activities, according to participants’ main reasons for practice; therefore, increasing their perception of quality, satisfaction, as well as their loyalty intention.Resumen: considerando las mejoras de la salud y las capacidades físicas como las razones principales de práctica, el crecimiento del número de participantes en centros de salud or fitness y las tendencias del fitness en 2018, el objetivo del presente trabajo es analizar los beneficios de cinco programas diferentes de fitness [G1) dieta sin ejercicio; G2) dieta y entrenamiento de fuerza (EF); G3) dieta y entrenamiento de potencia de alta intensidad (EPAI; HIPT en inglés); G4) dieta y ciclismo indoor; G5) dieta y boxeo] en la salud y parámetros de aptitud física. Se crearon cinco grupos y los participantes fueron distribuidos aleatoriamente (desde G1 a G5: n = 50; 25 f, 33.96 ± 3.42 años). En un primer análisis, se utilizó el t test para muestras relacionadas para comparar cada grupo, en el pre- y post-test, en las variables dependientes. En un segundo análisis, se realizó un ANOVA de un factor para comparar entre diferentes grupos, en el pre- y post- test, también seleccionando las variables dependientes, y seguido por un test post-hoc cuando se detectaron diferencias significativas entre grupos. Cuando la principal razón de práctica fue la pérdida de peso o masa grasa, el EPAI y el boxeo produjeron mejores resultados. Para el incremento de masa muscular, el EF presentó mejores resultados. En los parámetros de aptitudes físicas, el EF fue la actividad que presentó mejores resultados en el incremento de la menor fuerza explosiva y la mayor fuerza máxima, con diferencias estadísticamente significativas entre el pre- y post- test. Los monitores de fitness pueden usar esta información para adaptar, elegir y prescribir actividades adecuadas, de acuerdo con las principales razones de práctica de los participantes y, por lo tanto, aumentar su percepción de cualidad, satisfacción e intención de lealtad.